ANALISIS PENGARUH KUALITAS PELAYANAN, CITRA SEKOLAH, LINGKUNGAN SEKOLAH DAN KUALITAS TENAGA PENGAJAR TERHADAP KEPUASAN SISWA AL-HUDA PEKANBARU - rupat, herman (Eko dan Bisnis: Riau Economic and Business Review, 2019)
ABSTRACTThe four objectives of the present study aimed to find out: 1) the effect of service quality on students’ satisfaction of Senior High School Al-Huda Pekanbaru, 2)  the effect of school image on students’ satisfaction of Senior High School ofAl-Huda Pekanbaru 3) the effect of school environment on the students’ satisfaction of Senior High School Al-HudaPekanbaru,  4) the effect of teachers’professional quality of faculty on students’ satisfaction of Senior High School Al-HudaPekanbaru. Senior High School Al-Huda Pekanbaru was the setting of the study. The present study collected the primary and secondary data from Senior High School Al-Huda Pekanbaru. 162 students were involved as the research samples of the study. The technique of data analysis was descriptive and multiple linear regression analyses. The fulfillment of statistical assumptions was used (normality test, autocorrelation test, multi-coloniality test, heteroskedastic test, linearity test), and the hypothesis testing used were independent t-test, F test and determinant coefficient test. The study found that the service quality had a significant effect on students’ satisfaction. School image had no significant effect on students’satisfaction. School environment had a significant effect on students’satisfaction. The last,  teachers’ professional quality had a significant effect on students’satisfaction.